Rebirth of postidustrial architecture in polish towns. Adaptation of a historic building of a power station into a modern art galery in Radom = Renesans architektury postindustrialnej w polskich miastach. Adaptacja zabytkowego budynku elektrowni na Centrum Sztuki Współczesnej w Radomiu - Gaweł, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The transformation of city centres in Poland has taken various forms over the last 20 years. The specificity of the physiognomy and historic-spatial conditions imposes a certain direction of those transformations. They shape the public space of the modern towns and cities starts with glass-sky-scrapers to various forms of revitalisation of old buildings.
Keywords: architektura postindustrialna; architektura przemysłowa; adaptacja; renowacja; postindustrial architecture; industrial architecture; adaptation; renovation